2021
DOI: 10.3389/fphar.2021.739603
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam Protects Against LPS-Induced Endotoxicity Improving Survival of Endotoxemia Mice

Abstract: Remimazolam is a new benzodiazepine of sedative drugs with an ultra-short-acting anesthetic effect, commonly used for critically ill patients (especially septic patients) in intensive care units (ICUs). Although some anesthetics have been reported to show certain anti-inflammatory effects, the role of remimazolam in inflammation is still remained unknown. Here, we studied the effects of remimazolam on macrophage in response to LPS both in vivo and in vitro. Interestingly, compared with LPS treatment group, rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Currently, the preclinical literature involving remimazolam administration is scarce. Through TLR4 receptor downregulation, remimazolam was shown to interfere with lipopolysaccharide (LPS)-induced endotoxemia via blockade of NF-kB signaling pathway and reversal of LPS-induced phosphorylation of Akt and Erk protein kinases essential for neuronal survival [32 ▪▪ ]. The interaction with NF-kB was also beneficial in promoting glioma cell apoptosis in vitro [33] and in alleviating neuropathic pain in adult rats [34].…”
Section: Remimazolam: a Novel Ultra-short-acting Benzodiazepinementioning
confidence: 99%
“…Currently, the preclinical literature involving remimazolam administration is scarce. Through TLR4 receptor downregulation, remimazolam was shown to interfere with lipopolysaccharide (LPS)-induced endotoxemia via blockade of NF-kB signaling pathway and reversal of LPS-induced phosphorylation of Akt and Erk protein kinases essential for neuronal survival [32 ▪▪ ]. The interaction with NF-kB was also beneficial in promoting glioma cell apoptosis in vitro [33] and in alleviating neuropathic pain in adult rats [34].…”
Section: Remimazolam: a Novel Ultra-short-acting Benzodiazepinementioning
confidence: 99%
“…Additionally, upregulated pro-inflammatory cytokine expression may lead to hyperalgesia and further cause sensitization of the central and peripheral nervous system, affecting cognitive capabilities [ 20 ]. In previous studies, remimazolam has been shown to decrease the inflammatory response in LPS-induced endotoxicity [ 21 ], reduce neuropathic pain by regulating autophagy and bradykinin receptor B1. The ameliorating effects of remimazolam on hemodynamic stability are also well recognized [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[50] Remimazolam, an ultrashort-acting benzodiazepine, ameliorated the LPS-induced peripheral blood septic response in mice, reduced the number of LPS-induced deaths, and decreased the production of inflammatory factors in cultured macrophages in vitro. [51] In contrast, animal studies have shown that remimazolam can cause behavioral abnormalities and neuronal degeneration in mice. [52]…”
Section: Resultsmentioning
confidence: 99%